The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1365-2133.2010.09984.x
|View full text |Cite
|
Sign up to set email alerts
|

How stress gets under the skin: cortisol and stress reactivity in psoriasis

Abstract: Results suggest that daily stressors influence disease outcome in patients with psoriasis by affecting cortisol levels at moments of high stress. Furthermore, patients with persistently high levels of stressors seem to have a specific psychophysiological profile of lowered cortisol levels and may be particularly vulnerable to the influence of stressors on their psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 33 publications
8
100
0
4
Order By: Relevance
“…Evers et al, found psoriasis patients had significantly lower cortisol levels at moments when daily stressors are at peak levels. The study also reported that psoriasis patients with overall high levels of daily stressors exhibited lower mean cortisol levels, as compared to psoriatics with overall low levels of daily stressors (Evers et al, 2010) (Zangeneh et al, 2008). These blunted HPA axis and elevated SAM system responses to stress may be crucial in better understanding the inflammatory characteristics of psoriasis, particularly in stress-responders.…”
Section: Psoriasis and Stressmentioning
confidence: 98%
See 1 more Smart Citation
“…Evers et al, found psoriasis patients had significantly lower cortisol levels at moments when daily stressors are at peak levels. The study also reported that psoriasis patients with overall high levels of daily stressors exhibited lower mean cortisol levels, as compared to psoriatics with overall low levels of daily stressors (Evers et al, 2010) (Zangeneh et al, 2008). These blunted HPA axis and elevated SAM system responses to stress may be crucial in better understanding the inflammatory characteristics of psoriasis, particularly in stress-responders.…”
Section: Psoriasis and Stressmentioning
confidence: 98%
“…These blunted HPA axis and elevated SAM system responses to stress may be crucial in better understanding the inflammatory characteristics of psoriasis, particularly in stress-responders. For instance, decreased secretion of cortisol and increased levels of epinephrine (Zangeneh et al, 2008) and norepinephrine may stimulate the release of mast cells, affect skin barrier function, and upregulate proinflammatory cytokines, which could thereby maintain or exacerbate psoriasis severity (Evers et al, 2010). Some authors have commented that this decreased cortisol response may be similar to how psoriasis flares with steroid withdrawal, as evidenced by the well known phenomena of steroid-induced psoriasis rebound (Richards et al, 2005).…”
Section: Psoriasis and Stressmentioning
confidence: 99%
“…The relationship between stress and the course of a condition could in part be explained by the role that the immune system plays in chronic inflammatory skin diseases. More specifically, neuroendocrine and immune mechanisms (for example cortisol and cytokines) can be influenced by stress and can in turn influence chronic skin-related inflammatory activity [22,24]. Indeed, several prospective studies found a link between stressors and the course of conditions [23 -25].…”
Section: Psychosocial Factors In Dermatological Conditionsmentioning
confidence: 99%
“…Accordingly, in patients with atopic eczema, subjective stress proved to predict disease severity on the following day [26]. Additionally, in patients with psoriasis, high levels of daily stressors were associated with an increase in disease severity and itch four weeks later [24,25]. Stressors can influence wound healing [27], although this relationship has not been studied in patients with skin conditions.…”
Section: Psychosocial Factors In Dermatological Conditionsmentioning
confidence: 99%
“…az egyéb pszichoszomatikus hátterű (például krónikus fejfájás, essentialis hypertensio, irritábilis bél szindróma, rheumatoid arthritis, asztma, fi bromyalgia) betegségek-hez hasonlóan, a pikkelysömörös betegekben is az átlag-populációnál magasabb (8-10% vs. 15-51%) [12,14,15,16,17,18,19,20,21,22,23,24]. Taylor szerint az érzelmek szerepe többek között a megfelelő stresszpercepció kialakítása és ezáltal a viselkedésnek a sikeres alkalmazkodás érdekében a környezeti igényekhez történő alakítása [25].…”
Section: Conrad éS Mtsai [24]unclassified